Technical Review and Comparative Evaluation for the Selection of the Best Power Generation Technology from Waste in Kabul City - Mohsini, Mohammad Shuaib; Rahmany, Nisar Ahmad (Journal of Natural Sciences – Kabul University, 2023)
This research aims to identify the best method for urban waste management in Kabul, the capital city of Afghanistan. Urban development and constant population growth in Kabul have led to an increase in urban waste. According to 2018 statistics, Kabul produces an average of 3,050 tons of waste daily. This study first examines effective methods of energy extraction from waste, followed by the characteristics and specifications of each method. Subsequently, appropriate technologies for waste management are investigated, taking into account the social and cultural characteristics of Kabul's citizens and feasibility studies. The results indicate that the waste incineration approach will be more efficient, and constructing a waste incinerator is a suitable solution for managing urban solid waste in Kabul City.